Mexico : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper considers the 'informal sector' in Mexico. In Mexico and many other countries, the informal sector represents a large share of total employment. The paper reviews the literature on informality, with special focus on findings for Mexico, and develops a theoretical model that highlights the importance of externalities and the distortion associated with the informal sector. The analysis provides insight into the kinds of policy measures that might sustainably reduce the size of the informal sector. The paper analyzes financial saving in Mexico.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet